What's Left in Her Wake: In Honor of Adrienne Asch - Emens, Elizabeth F. (The Hastings Center report, 2014)
In 1987, Adrienne Asch published a short essay entitled “What's Missing (or What I Haven't Found Yet).” The essay sketched an agenda for future research in disability studies by cataloguing the questions she wished had been answered and the research she wished had been conducted thus far in the field. My tribute to Adrienne, written just over twenty-five years later, charts a similar path. In this short essay, I will not rehearse the questions that Adrienne set out in the pages of the Disability Studies Quarterly in 1987. Nor will I highlight the many ways the gaps in the field have been partially filled in the intervening years, as Adrienne surely appreciated by the time of her death. I will instead follow Adrienne's inspiring example of asking hard questions.